Accelerating the discovery of new dielectric properties in polymer insulation - Du, Boxue, 1961- (Engineering Science Reference, 2017)
"This book includes many aspects of power system insulation, some of which are quite different from each other. It focuses on insulators in high-speed railway system which required new dielectric properties different from traditional power system, polymer insulation exposed to multi-field in HVDC power system provided clues for the discovery of new polymer materials, and other topics"-- Provided by publisher.
Keywords: Electric insulators and insulation -- Polymers.; Dielectric devices.; elektronické knihy; electronic books